Stripy patterns in low-Re turbulent plane Couette flow - Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S. (IUTAM Bookseries, 2010)
We present for the first time a complete bifurcation diagram of plane Couette flow based on direct numerical simulation of the full Navier-Stokes equations. The use of an unusually large computational domain (800h×2h×356h) is crucial for the determination of transition thresholds, because it allows to reproduce spatiotemporal intermittency structures such as transient spots, turbulent bands, and laminar holes. The threshold in Re (based on the half-gap) is found to be Rec = 324±1, in very good agreement with available experimental data. This work points out that, at the onset of transition in Re, fragmented oblique patterns always emerge from the interaction of growing neighbouring spots. An analogy with thermodynamical phase transition seems relevant to describe the whole transition process. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21